Study of pre-stability of two dermocosmetic forms of topical application with aqueous extract of Bactris Guineensis - Mendoza-Torres, Andrés (2019)
Nowadays, there are more and more consumers looking for cosmetics that contains natural products, however the re-search in this area is limited, and with the current regulations it is necessary to show that dermocosmetics are stable during lifetime of the product. Therefore the objective of the research is to know physicochemical properties of Bactris guineensis extract to formulate a dermocosmetic gel form and another in cream form and determine pre-stability with the extract. Physicochemical analysis of Bactris guineensis lyophilized aqueous extract were made, then the cream and gel formulations were produce and finally a pre-stability test consisting of centrifuge at 3000 rpm for 30 minutes was applied. The results showed stability in the two formulations. The cream is chosen due to the wide use of this dermocosmetic form in other extracts such as achiote (Bixa orellana), bloodsucker (Oenothera rosea), culantro (coriandrum sativum), passion fruit (Passiflora edulis), tomato (Lycopersicum esculentum, Solanáceae) and arazá (Eugenia stipitata, Myrtáceae), Piperaceae (Piperaduncum L.), ishpingo (Ocotea quixos), cacao (Theobroma cacao l.), silver herb (Equisetum bogotense) and Pear ( pyrus communis), Talipariti elatum Sw.